Extracellular Cyclophilin A, Especially Acetylated, Causes Pulmonary Hypertension by Stimulating Endothelial Apoptosis, Redox Stress, and Inflammation - Chao Xue; Mark P. Sowden; Bradford C. Berk (2017)
Objective— Oxidative stress and inflammation play key roles in the development of pulmonary arterial hypertension (PAH). Cyclophilin A (CypA) is secreted in response to oxidative stress and promotes inflammation and cardiovascular disease. Endothelial cell (EC) dysfunction is an early event in the pathogenesis of PAH. We evaluated the role of extracellular CypA in PAH and compared the effects of acetylated CypA (AcK-CypA, increased by oxidative stress) and CypA on EC dysfunction. Approach and Results— In transgenic mice that express high levels of CypA in EC specifically, a PAH phenotype was observed at 3 months including increased right ventricular systolic pressure, α-smooth muscle actin expression in small arterioles, and CD45-positive cells in the lungs. Mechanistic analysis using cultured mouse pulmonary microvascular EC and human pulmonary microvascular EC showed that extracellular CypA and AcK-CypA stimulated EC inflammatory signals: increased VCAM1 (vascular cell adhesion molecule 1) and ICAM1 (intercellular adhesion molecule 1), phosphorylation of p65, and degradation of IkB. Extracellular CypA and AcK-CypA increased EC apoptosis measured by TUNEL (terminal deoxynucleotidyl transferase dUTP nick-end labeling) staining, Apo-ONE assay, and caspase 3 cleavage. Oxidative stress stimulated CypA and AcK-CypA secretion, which further promoted EC oxidative stress. AcK-CypA, compared with CypA, stimulated greater increases in apoptosis, inflammation, and oxidative stress. MM284, a specific inhibitor of extracellular CypA, attenuated EC apoptosis induced by CypA and AcK-CypA. Conclusions— EC-derived CypA (especially AcK-CypA) causes PAH by a presumptive mechanism involving increased EC apoptosis, inflammation, and oxidative stress. Our results suggest that inhibiting secreted extracellular CypA is a novel therapeutic approach for PAH.